Pelaksanaan Perlindungan Tenaga Kerja Anak dalam Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan Dihubungkan dengan Pasal 28b Ayat (2) Undang-Undang Dasar 1945 - Evariana, Dian (Lembaga Yasin AlSys, 2023)
The entry of children into the work area then initiated the government to make specific regulations as stated in Law Number 13 of 2003 concerning Manpower. In this Law, the problem of employing children is in articles 68-75, all of these articles are essentially an attempt to protect against a work system that is detrimental to the physical and mental development of children. This condition is sufficient to provide reasons for the authors to carry out scientific research related to the behavior of employing children in relation to Law no. 13 of 2003. More specifically, the author tries to analyze Articles 68-75 which contain arrangements for child employment. As for the purpose of this study is to find out how the regulations regarding the protection of child labor in the city of Serang, to find out how the implementation of articles 68-75 of law number 13 of 2003 concerning employment is related to article 28 b of the 1945 constitution concerning labor protection children in Serang City and to find out how the efforts made by the government in protecting child labor in Serang City. The research method used by the author is analysis because this research is qualitative in nature which is based on various literary sources and other documents relevant to the research material. The summary of the results of this research is that special protection for these children is based on the reality that children are human beings who are not perfect physically or mentally. This behavior, for example, involves recruiting children at relatively young ages, giving inappropriate wages, excessive working hours and no special protection in the process of working children.